2023
DOI: 10.1101/2023.01.05.23284237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria diagnosis in rural healthcare facilities and treatment-seeking behavior in malaria endemic settings in western Kenya

Abstract: Accurate diagnosis and timely treatment are central requirements for effective malaria management in communities. However, in resource-constrained settings, healthcare facilities are likely to be few, inaccessible, and ill-equipped with frequent drug or rapid diagnostic test kit (RDT) shortages. This may jeopardize much-needed quality care for patients and may have an impact on treatment-seeking behavior among the local population. The study’s goal is to determine treatment-seeking behavior, malaria diagnosis … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Studies conducted in Nigeria have shown that compared with public health facilities, PPMVs are the preferred source of malaria treatment for many people due to their proximity and longer operating hours and that they play a critical role in the provision of ACTs for malaria treatment (31,32). A study conducted in Tanzania revealed that PPMVs were the most common health facility providers visited for fever-related illnesses, including malaria, in rural areas (33,34). Similarly, a study in Kenya showed that PPMVs were the most commonly used healthcare providers for malaria treatment, especially in rural areas with limited access to healthcare facilities (35).…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Nigeria have shown that compared with public health facilities, PPMVs are the preferred source of malaria treatment for many people due to their proximity and longer operating hours and that they play a critical role in the provision of ACTs for malaria treatment (31,32). A study conducted in Tanzania revealed that PPMVs were the most common health facility providers visited for fever-related illnesses, including malaria, in rural areas (33,34). Similarly, a study in Kenya showed that PPMVs were the most commonly used healthcare providers for malaria treatment, especially in rural areas with limited access to healthcare facilities (35).…”
Section: Introductionmentioning
confidence: 99%